Under-Utilization of Female Capital: A Quantitative Study in Pakistani Perspective (International Journal of Business, Economics and Management, 2018)
This article examines the main obstacles faced by graduate females in Pakistan in pursuing their career due to which Pakistan is facing the critical situation like underutilization of female capital in Pakistan. This article explores the main hurdles that restrict the career development of graduated females in Pakistan and this is very important female capital goes wasted. The main purpose of this paper is to get to know why there is underutilization of female capital in Pakistan. The purpose of this paper is to explore the obstacles faced by Pakistani women in pursuing their careers because due to this reason there is underutilization of female capital in Pakistan. Respondents are graduate females who are not doing job after earning their graduate degree from well renowned universities. Sample size taken is of 300 respondents. The questionnaire were distributed and collected personally by the researcher. Some of the questionnaires were also emailed but it was assured that privacy will be maintained and names of the respondents will never be disclosed as this questionnaire is used for research purpose only. SPSS software is used for data analysis in this paper. Descriptive statistics is done in SPSS software. The findings show that male’s attitude words female at workplace or out of the workplace is the main obstacle in purposing job career in Pakistan. Whereas at workplace such as the administration of government agencies men treat female in different way on contrast to their male colleagues (McElwee and Al-Riyami, 2003) even sometimes females are teased, bad comments are passed over them. Due to this reason many of the families do not allow their daughters, wives and sisters to go outside for job. Other obstacles that are hindering the way of female job career development are culture, families and obviously workplace environment or job requirements. Others variables like lack of confidence and religion’s results showed that these variables are no hindering females anymore from doing job in Pakistan. Due to time constraints sample of only 300 respondents was taken but this issue needs to be took into consideration at broader and macro level as it is a micro level study. Recommendations It is suggested that Government of Pakistan, different NGOs, private and public organizations should create a favorable workplace environment for female employees. It is also suggested that different awareness campaigns should be established so that males’ attitude i.e. a very big obstacle for females in pursuing their career should be minimized or eliminated. Originality/value – This paper fulfils an identified need to study how female capital could be utilized at its full potential so that economy of Pakistan could be boasted up.